KARAKTERISASI TANAH LEMPUNG GAMBUT KALIMANTAN SELATAN SEBAGAI BAHAN BAKU PEMBUATAN MEMBRANE SUPPORT - Muthia Elma; Isna Syauqiah; Nor Aldina; Hesti Kesumadewi (Faculty of Industrial Technology Universitas Islam Indonesia, 2016)
Inorganic materials (such as silica and alumina) is a material that is very important and the most desirable in the field of membrane technology. This is due to the physical characteristics and permeation properties owned by the two materials is much better when compared to other polymerbased material. Alumina, for example, this material mostly can be found in clay, and the price is much cheaper as well as easy to find if compared to silica material. The use of peat clay as raw material to produce alumina as membranes support from natural materials would save production costs. This material is also easy to find in South Kalimantan especially around the wetland areas. The aim of this study is to characterize the peat clay as raw material to fabricate membranes module (membranes support). The method is by drying the clay material in uniform particle size (monosize). The raw material powder is then mixed with the organic additives. This organic content provide the hydrophilicity and prorosity agent. Furthermore, it then was calcined and characterized to determine the functional group of the material weather it is more hydrophilicity and porosity. The result shows that the addition of H2O and starch content of functional groups affect the content of the Si-O-Si and Si-O-Al groups on clay material. The content of Si-O-Si and Si-O-Al decreases if content of H2O and starch is higher. It is shown that the streching the Si-OH groups that are more hydrophilic transform into Si-O-Si and Si-O-Al groups that are more hydrophobic. Therefore, the calcined material will be more hydrophobic and more porous.